2011
DOI: 10.3390/ijerph8062109
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Association between Ambient Air Pollution and Daily Cardiovascular and Respiratory Mortality in an Urban District of Beijing

Abstract: The association between daily cardiovascular/respiratory mortality and air pollution in an urban district of Beijing was investigated over a 6-year period (January 2003 to December 2008). The purpose of this study was to evaluate the relative importance of the major air pollutants [particulate matter (PM), SO2, NO2] as predictors of daily cardiovascular/respiratory mortality. The time-series studied comprises years with lower level interventions to control air pollution (2003–2006) and years with high level in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 52 publications
5
43
2
1
Order By: Relevance
“…Daily SO 2 and NO 2 concentrations had clear seasonality, with peak concentrations occurring during the winter. Daily patterns for the concentrations of SO 2 and NO 2 in this study were consistent with previous studies (Zhang et al 2011a;Zhang et al 2011c). The pollutant concentrations were typically higher during the winter from November to the following March (Zhang et al 2011c).…”
Section: Discussionsupporting
confidence: 92%
“…Daily SO 2 and NO 2 concentrations had clear seasonality, with peak concentrations occurring during the winter. Daily patterns for the concentrations of SO 2 and NO 2 in this study were consistent with previous studies (Zhang et al 2011a;Zhang et al 2011c). The pollutant concentrations were typically higher during the winter from November to the following March (Zhang et al 2011c).…”
Section: Discussionsupporting
confidence: 92%
“…In the period January 14 -July 14, total pollen excluding Ambrosia pollen indicates very low weights for each category involving an indifferent role in severe asthma attacks (Table 2c). Results received for the period July 15 -October 16 (Table 2a) indicating significant positive associations between pollen levels and the patient numbers, are similar to those found [77,81,82].…”
Section: Season Ofsupporting
confidence: 78%
“…Previous findings concerning the role of SO 2 seem inconsistent. This pollutant was not significantly associated with respiratory diseases by [38,65], but other studies reported positive relationships [30,65,66,77].…”
Section: Season Ofmentioning
confidence: 63%
See 1 more Smart Citation
“…These diseases are prevalent in China, where air pollution levels are often orders of magnitude higher than those in developed countries (Zhang et al, 2011). Because PM deposition and related health effects depend on the particle size, PM 2.5 (fine particles with aerodynamic diameter ≤ 2.5 µm) and ultrafine particles (UFP; diameter < 100 nm) have been associated more strongly with health risk than PM 10 (Politis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%